Analisis Efisiensi, Efektivitas dan Kontribusi Pajak Daerah Serta Retribusi Daerah Terhadap Pendapatan Asli Daerah (Studi Kasus pada Kabupaten Ponorogo Tahun 2020 - 2024) - Mardika Putra, Bagas; Zulfa Wafirotin, Khusnatul; Wijayanti, Iin (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to analyze the efficiency, effectiveness, and contribution of regional taxes and levies to Regional Original Income (PAD) in Ponorogo Regency. The data in this study are secondary data in the form of the Regional Revenue and Expenditure Budget Realization Report (LRAPBD) of Ponorogo Regency for 2020-2024. The data analysis method in this study uses a quantitative descriptive method with analytical tools in the form of efficiency analysis, effectiveness analysis, and contribution analysis. The results of the analysis of the efficiency of regional taxes in Ponorogo Regency in 2020-2024 are on average very efficient with an average efficiency percentage of 4.24%. The results of the analysis of the efficiency of regional levies in Ponorogo Regency in 2020-2024 are on average very efficient with a percentage of 2.95%. The results of the analysis of the effectiveness of regional taxes in Ponorogo Regency in 2020-2024 are on average very effective with an average efficiency percentage of 113.20%. The results of the analysis of the effectiveness of regional levies in Ponorogo Regency in 2020-2024 are on average categorized as effective with a percentage of 99,91%. The results of the analysis of regional tax contributions to the Regional Original Income (PAD) of Ponorogo Regency in 2020-2024 are on average very good with an average contribution percentage of 32.28%. The results of the analysis of the contribution of regional levies to the Regional Original Income (PAD) of Ponorogo Regency in 2020-2024 are on average classified as insufficient with an average contribution percentage of 15.80%.